Feng Student Activities Management System (Feng Sams) - DOREAL DYOLEE ANAK DOMINIC, - (Universiti Malaysia Sarawak, 2022)
Student Management System is currently used widely in the academic institution. Most of the system is mainly used for academic matters in providing the information regarding academic. However, there is limited number of student management system that focused on student activities, especially for student club purposes. Therefore, in this project, it is emphasized in developing student management system for student club in Faculty of Engineering, UNIMAS. All the activities, which are organized by the clubs, are standardized in one main platform, which is the Student Activities Management System or SAMS. In order to develop the system, the coding language is PHP with the help of Adobe Dreamweaver, whereby HTML and CSS are utilized for styling and organizing the presentation of the webpage interface. From the results, this SAMS system has accomplished the project objective and it is then expected to be able to assist student clubs in managing their events, documents record and reports submission properly.